High fetal risk in pregnancies of myositis patients—a Hungarian cohort study - Nagy-Vincze, Melinda; Szinay, Dorottya; Szabó, Katalin; Molnár Deliné, Sarolta; Balkay, László; Béldi, Tibor; Griger, Zoltán (Frontiers in Lupus, 2024)
Background: Several systemic autoimmune rheumatic diseases (SARD) may affect both fetal and maternal outcomes in pregnancy. Little information is available regarding pregnancy outcomes in women with idiopathic inflammatory myopathy. Previously published articles stated that activity of maternal disease could lead to worse pregnancy outcome. A former multicenter study suggested that anti-Jo1 antibody positivity and joint involvement could distinguish a more vulnerable group considering pregnancy complications. Our aim was to find prognostic factors among clinical symptoms at disease onset and autoantibody profile for identifying a high-risk group for poor pregnancy outcome.Methods: Clinical data of myositis cohort of Division of Clinical Immunology, University of Debrecen, Hungary were reviewed retrospectively. IIM diagnosis was made by Bohan and Peter's criteria or EULAR/ACR criteria. Disease activity was evaluated based on physician opinion.Gynecological definitions have been used to evaluate fetal outcome.Results: Reviewing clinical data of overall 763 patients (542 women and 221 men) revealed that 5.2% of female patients had pregnancies in the same time or after myositis onset. 71.4% of the mothers suffered from Polymyositis (PM) and 28.6% from Dermatomyositis (DM). Their mean age at myositis diagnosis was 25.28 years and the average time between myositis diagnosis and first pregnancy was 55.4 months. Maternal complications were preeclampsia in one case and pregnancy induced myositis in 25% of cases. All pregnancy induced cases improved after immunosuppressive treatment. 28 patients reported overall 60 pregnancies, where multiple pregnancies occurred in 57%. Early or late fetal loss was detected in 41,7 % of the pregnancies, stillbirth in 18,3 % of labors. Although late fetal loss was observed mainly due to placental insufficiency in patients with anti-Jo1 positivity and complications seemed more frequent in PM form, logistic regression analysis only confirmed that multiple pregnancies could be independent risk factor of fetal (p:0.0112) and interstitial lung disease of maternal complications (p: 0.02).Internal organ involvement and number of pregnancies could influence pregnancy outcome in myositis patients. Patients' family planning should have to be well organized and counselled by myositis experts. Prospective, multicenter collaborations needed to precisely identify high-risk groups and state managing guidelines.